2012
DOI: 10.1089/met.2011.0098
|View full text |Cite
|
Sign up to set email alerts
|

Association of Metabolic Syndrome Parameters with TT3 and FT3/FT4 Ratio in Obese Turkish Population

Abstract: Metabolic syndrome frequency was increased in our study population compared to the general population. Metabolic syndrome parameters (except HDL) correlated with TT3, FT4, and the FT3/FT4 ratio. FT4 levels were associated with obesity and metabolic syndrome independently of insulin resistance, whereas TT3 levels were associated with both insulin resistance and metabolic syndrome. This relationship can be explained by compensatory effects of TT3, and probably FT4, on energy expenditure and thermogenesis in obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
3
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 33 publications
8
46
3
5
Order By: Relevance
“…Tarcin et al [29] reported higher FT4 levels and lower FT3/FT4 in obese subjects with metabolic syndrome than in those without. This supports the concept that inflammation and adiposity parameters are more associated with changes in thyroid hormone levels than glycaemic levels, as none of the subjects in this study had T2DM.…”
Section: Discussionmentioning
confidence: 97%
“…Tarcin et al [29] reported higher FT4 levels and lower FT3/FT4 in obese subjects with metabolic syndrome than in those without. This supports the concept that inflammation and adiposity parameters are more associated with changes in thyroid hormone levels than glycaemic levels, as none of the subjects in this study had T2DM.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, thyroid hormone disorders are associated with changes in body composition, and obesity may have an impact on the levels of thyroid hormones as well as the risk of MetS in women (9,29). Tarcin et al (30) showed that MetS positive patients had significantly higher fasting glucose, triglyceride, fT4, BP, and lower HDL and fT3/fT4 ratio than MetS negative patients. In our study, interestingly, MetS parameters, except systolic BP, were correlated with the fT3/fT4 ratio, (HDL negatively), significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to adults (2,15,18,(31)(32)(33), the role of thyroid hormones in glucose dysmetabolism in otherwise healthy obese children has been examined to a limited extent. In our pediatric population, both BMI-SDS and TSH variations were independently associated with HOMA-IR variation.…”
Section: δBmc-sdsmentioning
confidence: 99%